Characteristics of environmental RNAi in potato psyllid, Bactericera cockerelli (Sulc) (Hemiptera: Psylloidea: Triozidae) - Mondal, Mosharrof; Carver, Megan; Brown, Judith K. (Frontiers in Physiology, 2022)
RNA interference (RNAi) has potential to become a major tool for integrated management of insect pests of agricultural crops based on sequence-specificity and low doses of rapidly biodegradable dsRNA. Deploying ‘environmental RNAi’ for control of insect vectors of plant pathogens is of increasing interest for combatting emerging plant diseases. Hemipteran insect vectors, including psyllids, are vascular feeders, making their development difficult to control specifically target with pesticidal chemistries. Psyllids transmit “Candidatus Liberibacter solanacearum” the causal organism of potato zebra chip and tomato vein greening diseases, transmitted, respectively, by the potato or tomato psyllid (PoP). Until now, the optimal effective concentration(s) of double-stranded RNA (dsRNA) required for significant gene knockdown and RNAi persistence in PoP have not been determined. The objective of this study was to optimize RNAi in young PoP adults and 3rd instars for screening by oral delivery of dsRNAs. The minimal effective dsRNA concentrations required for robust knockdown and persistence were evaluated by delivering seven concentrations spanning 0.1 ng/µL to 500 ng/µL over post ingestion-access periods (IAP) ranging from 48 hr to 12 days. The PoP gene candidates evaluated as targets were vacuolar ATPase subunit A, clathrin heavy chain, and non-fermenting protein 7, which were evaluated for knockdown by qPCR amplification. The minimum and/or the second most effective dsRNA concentration resulting in effective levels of gene knockdown was 100 ng/µL for all three targets. Higher concentrations did not yield further knockdown, indicating potential RISC saturation at the higher doses. Gene silencing post-IAP of 100 ng/µL dsRNA persisted for 3-5 days in adults and nymphs, with the PoP 3rd instar, followed by teneral and mature adults, respectively, exhibiting the most robust RNAi-response.